Detection of discretized single-shell penetration in mesoscopic vortex matter - Dolz, Moira Ines (2014)
We investigated configurational changes in mesoscopic vortex matter with less than thousand vortices during flux penetration in freestanding 50 μm diameter disks of Bi2Sr2CaCu2O8+δ. High-resolution AC and DC local magnetometry data reveal oscillations in the transmittivity echoed in peaks in the third-harmonics magnetic signal fainting on increasing vortex density. By means of extra experimental evidence and a simple geometrical analysis we show that these features fingerprint the discretized entrance of single-shells of vortices having a shape that mimics the sample edge.